Challenges and opportunities for workforce skills in halal agri-food sector to meet global market demands through Halalink application - Indriani, Mutiara Rachmina; Arrahman, Naufal; Dini, Vianda Mayeri; Rahmawati, Yuli; Darmawan, Noviyan (IPB University, 2025)
Indonesia is the largest Muslim-majority country in the world and holds significant potential in halal food farming sector. The growing global demand for halal products offers vast opportunities to expand agricultural exports and meet the needs of both domestic and international markets. However, challenges such as a lack of skilled human resources, limited awareness of halal certification processes, and technological barriers, particularly among micro, small, and medium enterprises (MSMEs), hinder the industry growth. Therefore, this study aimed to develop